Vibroacoustic optimization using a statistical energy analysis model. (4th August 2016) - Culla, Antonio; D׳Ambrogio, Walter; Fregolent, Annalisa; Milana, Silvia
Abstract: In this paper, an optimization technique for medium-high frequency dynamic problems based on Statistical Energy Analysis (SEA) method is presented. Using a SEA model, the subsystem energies are controlled by internal loss factors (ILF) and coupling loss factors (CLF), which in turn depend on the physical parameters of the subsystems. A preliminary sensitivity analysis of subsystem energy to CLF׳s is performed to select CLF׳s that are most effective on subsystem energies. Since the injected power depends not only on the external loads but on the physical parameters of the subsystems as well, it must be taken into account under certain conditions. This is accomplished in the optimization procedure, where approximate relationships between CLF׳s, injected power and physical parameters are derived. The approach is applied on a typical aeronautical structure: the cabin of a helicopter. Abstract : Highlights: A system optimization technique for medium-high frequencies is presented. The technique is based on a SEA model. Most effective coupling loss factors (CLFs) are selected using sensitivity analysis. CLFs and injected powers are expressed as functions of physical parameters. The method is applied on a simplified model of a helicopter cabin.